Pengaruh Pengalaman Magang, Soft Skill Dan Hard Skill terhadap Kesiapan Kerja (Studi Kasus Pada Mahasiswa Angkatan 2021 Prodi Manajemen Fakultas Ekonomi Universitas Muhammadiyah Aceh) - Mimiasri Mimiasri; Abdul Halik; Siti Mujanah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of internship experience, soft skills, and hard skills on the job readiness of students from the 2021 Management Program at the Faculty of Economics, Universitas Muhammadiyah Aceh. The method used is a quantitative approach with multiple linear regression analysis. Data was collected through questionnaires completed by 63 students who have participated in internships. The results show that, partially, internship experience does not have a significant effect on job readiness, while both soft skills and hard skills do have a significant influence. Simultaneously, all three variables positively affect the students' job readiness. This research concludes that the development of soft skills and hard skills needs to be enhanced, while the quality of internship experiences should be improved to better align with industry needs.